(untitled) - Prothero, Mark (San Francisco, 2006)
After a two-decade investigation, Gary Ridgway, America's "most prolific serial killer," was arrested in November 2001. Prothero became one of his attorneys. A Seattle-area DNA expert who emerges as an affable and humble family man, Prothero argued successfully against the death penalty for Ridgway. Aided by veteran journalist Smith (The Search for the Green River Killer), Prothero probes the psyche of a monster who appeared to be a devoted husband, son and brother. Did Ridgway's mother corrupt him as a teenager when she washed his genitals after he wet the bed, or did years of inhaling paint fumes on the job impair his judgment? Prothero, who confronted the banality of evil when his miserly client explained that he killed some of his prostitute victims just to get his
Keywords: Serial murders,Tài liệu vụ giết người; Case studies,Học tập nghiên cứu; Washington (State), Green River (King Country),Hoa Kỳ